The Role of Customs in the Creation of Families - Tangirbergenova Mexriban Ko’shkinbaevna (Proceedings of The ICECRS, 2019)
This paper makes analyses of the role of family in Uzbekistan. Creation of customs is considered as a major point of the development in the society. Therefore, this paper makes conclusion both methodological and theoretical points in order to make better analyses as the whole